(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The species of Bombus Latreille and Psithyrus Lepeletier collected in an interesting protected area of Central Alps ("Parco Naturale dell’Adamello") are listed. They are 24 species (18 Bombus, 6 Psithyrus), besides two more Bombus captured just outside the border of Pàrco. This set of Bombinae can be considered complete for the investigated area and very important with regard to the preservation of the environment.